2018
DOI: 10.1093/icvts/ivy127
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for acute infective endocarditis: epidemiological data from a Spanish nationwide hospital-based registry†

Abstract: Surgical treatment in IE has trended upwards in Spain during the last 2 decades. Patients are getting older and more frequently experience organ dysfunction. Mortality ratio steadily declined without changes in the length of hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 26 publications
1
10
0
1
Order By: Relevance
“…In a study carried out in Spain, Olmos et al observed an increase in incidence, rising from 2.72 cases to 3.49 cases per 100,000 inhabitants/year during the period analysed (2003-2014) [10]. Likewise, Bustamante Munguira et al reported increased IE incidence in Spain, which rose from 3.17% in 1997 to 5.56% in 2014 [9]. In Denmark, Erichsen et al also observed a rise in incidence during 1994-2011, going from 3.93 to 7.55 cases per 100,000 inhabitants a year [11].…”
Section: Incidencementioning
confidence: 89%
See 3 more Smart Citations
“…In a study carried out in Spain, Olmos et al observed an increase in incidence, rising from 2.72 cases to 3.49 cases per 100,000 inhabitants/year during the period analysed (2003-2014) [10]. Likewise, Bustamante Munguira et al reported increased IE incidence in Spain, which rose from 3.17% in 1997 to 5.56% in 2014 [9]. In Denmark, Erichsen et al also observed a rise in incidence during 1994-2011, going from 3.93 to 7.55 cases per 100,000 inhabitants a year [11].…”
Section: Incidencementioning
confidence: 89%
“…Bustamante Munguira et al, analysing the Spanish series during the time period 1997-2014, found that the percentage of patients requiring surgery increased over the course of the study, reaching 15.7% of the patients [9]. These figures are much lower than those of the European registry, in which the Euro Heart Survey reported a rate of 58.7% [29].…”
Section: Indication For Surgery In Left-sided Aortic Valve Endocarditismentioning
confidence: 93%
See 2 more Smart Citations
“…After antibiotics were introduced in clinical practice in 1928 by Sir Alexander Fleming, the mortality of the disease dramatically dropped (3) . However, despite new and improved antibiotics, mortality remains high, between 10 and 25% according to published series (4)(5)(6)(7)(8)(9)(10)(11) .…”
Section: Introductionmentioning
confidence: 99%